Continuous Remote Monitoring in Hazardous Sites Using Sensor Technologies. (10th July 2012) - Manes, Gianfranco; Collodi, Giovanni; Fusco, Rosanna; Gelpi, Leonardo; Manes, Antonio
Abstract : The deployment of a distributed point source monitoring system based on wireless sensor networks in an industrial site where dangerous substances are produced, used, and stored is described. Seven essential features, fundamental prerequisites for our estimating emissions method, were identified. The system, consisting of a wireless sensor network (WSN) using photoionisation detectors (PIDs), continuously monitors the volatile organic compound (VOC) concentration at a petrochemical plant on an unprecedented time/space scale. Internet connectivity is provided via TCP/IP over GPRS gateways in real time at a one-minute sampling rate, thus providing plant management and, if necessary, environmental authorities with an unprecedented tool for immediate warning in case critical events happen. The platform is organised into subnetworks, each including a gateway unit wirelessly connected to the WSN nodes. Environmental and process data are forwarded to a remote server and made available to authorized users through a rich user interface that provides data rendering in various formats, in addition to worldwide access to data. Furthermore, this system consists of an easily deployable stand-alone infrastructure with a high degree of scalability and reconfigurability, as well as minimal intrusiveness or obtrusiveness.